2022
DOI: 10.3390/mi13040505
|View full text |Cite
|
Sign up to set email alerts
|

An Endovascular Catheterization Robotic System Using Collaborative Operation with Magnetically Controlled Haptic Force Feedback

Abstract: Robot-assisted technology is often used to perform endovascular catheterization surgeries, which generally depend on the flexible operability and the accurate force feedback of a robotic system. In this paper, an endovascular catheterization robotic system (ECRS) was developed to improve collaborative operation and haptic force feedback. A couple of operating handles were designed to maximize the use of the natural operations of surgeons on the master side, which is a flexible and ergonomic device. A magnetica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Based on the results of our overview, many efforts have been made to overcome the technological limits of CAS surgery. Nonetheless, a research gap between dental/maxillofacial surgery and other surgical specialties such as endovascular treatments, laparoscopic surgery, and microsurgery needs to be stressed [51][52][53]. Furthermore, this work is intended to resemble technological trends in haptic transducing mechanisms in maxillofacial and dental surgery applications.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of our overview, many efforts have been made to overcome the technological limits of CAS surgery. Nonetheless, a research gap between dental/maxillofacial surgery and other surgical specialties such as endovascular treatments, laparoscopic surgery, and microsurgery needs to be stressed [51][52][53]. Furthermore, this work is intended to resemble technological trends in haptic transducing mechanisms in maxillofacial and dental surgery applications.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, scenes like this have transcended the realm of science fiction. With the advancement of microrobots, their applications have become widespread, particularly in the medical field with micro-/nano-manipulation [189][190][191], as shown in Figure 5.…”
Section: Applications Of Magnetic Microrobotsmentioning
confidence: 99%
“…The in vitro experimental results showed that the haptic feedback based on catheter was helpful for improving intubation skills and reducing the cognitive workload of operators. Li et al [ 107 ] used similar principles to develop a collaborative control platform based on magnetorheological fluid and hydrogel modeling that could replicate operator movements while providing haptic force feedback. Payne et al [ 48 ] developed a “hands-on” master–slave control system that used voice-coil motors to provide force feedback to the operator.…”
Section: Key Technologies and Application Areas Of Vascular Intervent...mentioning
confidence: 99%